2022
DOI: 10.1037/pspp0000382
|View full text |Cite
|
Sign up to set email alerts
|

The role of temperament in the onset of suicidal ideation and behaviors across adolescence: Findings from a 10-year longitudinal study of Mexican-origin youth.

Abstract: Suicide among young people is an increasingly prevalent and devastating public health crisis around the world. To reduce the rate of suicide, it is important to identify factors that can help us better predict suicidal ideation and behaviors. Adolescent temperament (Effortful Control, Negative Emotionality, Positive Emotionality) may be a source of risk and resilience for the onset of suicidal ideation, plans, and attempts. The present study uses longitudinal data from a large, community sample of Mexican-orig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 101 publications
(182 reference statements)
1
17
0
1
Order By: Relevance
“…In our prospective study of Mexican-origin youths, we conducted annual assessments of STBs beginning at age 10. Our first article on STBs in Mexican-origin youths (Lawson et al, 2022) documented increases over early adolescence that peaked between 14 and 15 years, mirroring the developmental trajectory of adolescent STBs in other ethnic groups (Nock et al, 2013). Focused on temperamental predictors of STBs, that study revealed that effortful control was associated with decreased probability of STBs by Mexican-origin youths, whereas negative emotionality (e.g., aggression, frustration, depressed mood) was associated with increased likelihood of STBs.…”
Section: Development Of Stbs In Adolescencementioning
confidence: 86%
“…In our prospective study of Mexican-origin youths, we conducted annual assessments of STBs beginning at age 10. Our first article on STBs in Mexican-origin youths (Lawson et al, 2022) documented increases over early adolescence that peaked between 14 and 15 years, mirroring the developmental trajectory of adolescent STBs in other ethnic groups (Nock et al, 2013). Focused on temperamental predictors of STBs, that study revealed that effortful control was associated with decreased probability of STBs by Mexican-origin youths, whereas negative emotionality (e.g., aggression, frustration, depressed mood) was associated with increased likelihood of STBs.…”
Section: Development Of Stbs In Adolescencementioning
confidence: 86%
“…A greater understanding of the burden and the determinants of suicide deaths in adolescents is important in order to reduce the problem. According to the Global School-Based Student Health Survey [7], the prevalence of suicide ideation is significantly greater in females than males, in contrast to the prevalence of attempt that did not show differences by sex or age. This study also identified being bullied and not having close friends as factors associated with ideation and attempt.…”
Section: Introductionmentioning
confidence: 89%
“…Some studies in Mexican youth have examined suicide attempt and associated factors in adolescents. A ten-year longitudinal study evaluated annually the association of temperament with suicide ideation in Mexican origin youth beginning at age 12 [7] finding high levels of effortful control and low levels of negative emotionality associated with decreased probability of first onset of suicide ideation, plans, and attempts. A national study conducted in 2007 among a representative sample of students ages 14-19 from public schools, reported the following factors related to suicide attempt: sexual abuse (OR = 1.57), depressive symptoms (OR = 1.51), tobacco use (OR = 2.57), alcohol use (OR = 1.31) and, for women only, having had sexual relations (OR = 1.65) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Maser et al ( 9 ) found that completion of suicide within 12 months was predicted by clinical variables such as substance use or anxiety, while completion of suicide beyond 12 months was better predicted by temperamental factors such as impulsivity. Other characteristics previously found to be associated with suicide attempt include negative emotionality and neuroticism ( 10 , 11 ). However, there are limited studies examining temperamental risk factors in adolescents.…”
Section: Introductionmentioning
confidence: 99%